MULTIFUNCTIONAL AGRICULTURE, PROTECTIONISM,AND PROSPECT OF TRADE LIBERALIZATION - 문완기 (2010)
The concept of multifunctional agriculture has been suspected of 'disguised' or 'veiled' protectionism by proponents of market-oriented reforms since the Uruguay Round Agreement on Agriculture(URAA). In this article, I review the history and nature of agricultural protectionism and probe the concept of multifunctional agriculture from economics and broader social science perspectives. Then, I contend that agricultural protectionism in the second half of the 20th century was, in fact, a revelation of the demand for the multifunctional roles of agriculture, heightened by industrial policies designed by developed countries to secure the survival and growth of agriculture to a socially acceptable point. An implication of this contention is that we are not likely to have a trading system in agriculture as liberalized as manufacturing/industrial sectors. The frame of debate for agricultural trade is neither protectionism vs. trade liberalization nor market vs. government any longer. I propose that the relevant frame should be centered around the question of how to fine-tune government interventions and the WTO’s trade rules to better serve agriculture-related goals unique to each country across the world. The traffic light box system from the Uruguay Round signified a starting point of promising mechanism that could harmonize market rules with the social demand for multifunctional and sustainable agriculture. The negotiators in the WTO multilateral talks should discard the perception that it is always a virtue to liberalize agricultural trade.
Keywords: agricultural protectionism; multifunctional agriculture; WTO; trade liberalization; Green Box; Uruguay Round; Doha Development Round; agricultural protectionism; multifunctional agriculture; WTO; trade liberalization; Green Box; Uruguay Round; Doha Development Round